THE ANALYSIS OF ENGLISH PRONUNCIATION TEACHING METHOD IN ONE OF TANGERANG VOCATIONAL HIGH SCHOOL - Gustary, Devian Try (ReALL - Research on Applied Linguistics and Literature, 2023)
Pronunciation is the way in which a word is pronounced, or the act of producing the sounds of speech, including articulation, stress, and intonation. There are many methods that can be used to teach pronunciation. Teacher can use, songs, drilling, visual aids, and so on. The aims of this research are to know what method that used by a teacher in teaching English pronunciation, and what are the factors that cause students difficulties in learning English pronunciation. The writer used descriptive qualitative which is the data derived from observation, questionnaire, and interview. In this research the writer found two methods used by the teacher when teaching English pronunciation which are drilling and song method, besides that there are four factors that cause students difficulties in learning English pronunciation which are difficulty in learning English pronunciation is associated with hearing; difficulty in learning how foreign sounds with speech organs; difficulty in knowing a word whose sound distribution is the correct sound to say; difficulty in remembering a word whose sound distribution is the correct sound to say.